Evaluating the Configuration of Space at SMK Negeri 12 Malang Utilizing Spatial Syntax - Hanif, Muhammad Ziadan; Maulana, Rizqi; Yenitasari, Dini; Daniswara, Alyaa; Mutiara, Elok (Proceedings of the International Conference on Green Technology; Vol 14 No 1 (2024): Proceeding of 14th International Conference on Green Technology, 2025)
These instructions give you basic guidelines for preparing papers for conference proceedings. SMKN 12 Malang is located at Jl. Pahlawan, Balearjosari, Kec. Blimbing, Malang City, East Java 65126. This school results from the function transfer from SMA Negeri 12 Malang. Previously, this high school had also experienced a change of location in a relatively short period of time. An evaluation of the spatial configuration of SMKN 12 Malang showed that the transfer of the building from SMA to SMK without careful spatial planning had a significant impact on the quality of the learning environment. Using the Space Syntax method, this research aims to analyze the connectivity, integration, and intelligibility of the existing and proposed spatial layouts. The results showed that the existing layout had several shortcomings regarding connectivity and space utilization efficiency. Simulation and re-analysis resulted in the proposal of a new, more optimized layout. The evaluation of the proposed layout showed significant improvements in all three aspects studied, so it can be concluded that the application of Space Syntax principles has the potential to create an effective and efficient learning environment.